2005
DOI: 10.1016/j.jvs.2005.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Amplatzer Vascular Plug to occlude the internal iliac arteries in patients undergoing aortoiliac aneurysm repair

Abstract: The Amplatzer Vascular Plug allows for a cost-effective method to occlude the internal iliac artery in patients undergoing endograft repairs of aortoiliac aneurysms. The use of a single device with a precise placement at the origin of the artery minimizes cost and avoids ischemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 21 publications
3
67
0
4
Order By: Relevance
“…It is based on statewide data collection by individual data organizations across the USA and includes the largest collection of longitudinal hospital care data in the USA, encompassing all-payer, discharge-level information. The other AE and complication-related treatment cost data were obtained using the published literature [16][17][18][19]. These cost estimates were then inflated to 2016 (October) US dollars using the Medical Care Component of the Consumer Price Index [20].…”
Section: Cost End Pointsmentioning
confidence: 99%
“…It is based on statewide data collection by individual data organizations across the USA and includes the largest collection of longitudinal hospital care data in the USA, encompassing all-payer, discharge-level information. The other AE and complication-related treatment cost data were obtained using the published literature [16][17][18][19]. These cost estimates were then inflated to 2016 (October) US dollars using the Medical Care Component of the Consumer Price Index [20].…”
Section: Cost End Pointsmentioning
confidence: 99%
“…This device allows a more precise proximal embolization (ProxEmbX) in comparison with embolization with several coils. 1 Recent studies demonstrated that the AVP is a suitable alternative to coil embolization to achieve successful occlusion of the IIA before EVAR. [9][10][11][12] Isolated AVP embolization seems to be reasonable in case of an unaffected IIA.…”
Section: Endovascular Aneurysm Repair (Evar) Is An Established Alternmentioning
confidence: 99%
“…The successful use of vascular plugs has been reported in similar scenarios. 8) However this is dependent on favourable aneurysm morphology and access. In addition factors such as experience of the interventional team and case volume load of acute presentations have been identified from trials on ruptured aortic aneurysm as a major determinant of a successful outcome.…”
Section: Case Presentationmentioning
confidence: 99%